DNA barcoding of echinopluteus larvae uncovers cryptic diversity in neotropical echinoids. Issue 2 (13th June 2020) - Collin, Rachel; Venera‐Pontón, Dagoberto E.; Driskell, Amy C.; Macdonald, Kenneth S.; Geyer, Laura B.; Lessios, Harilaos A.; Boyle, Michael J.
Abstract: Surveys of larval diversity consistently increase biodiversity estimates when applied to poorly documented groups of marine invertebrates such as phoronids and hemichordates. However, it remains to be seen how helpful this approach is for detecting unsampled species in well‐studied groups. Echinoids represent a large, robust, well‐studied macrofauna, with low diversity and low incidence of cryptic species, making them an ideal test case for the efficacy of larval barcoding to discover diversity in such groups. We developed a reference dataset of DNA barcodes for the shallow‐water adult echinoids from both coasts of Panama and compared them to DNA sequences obtained from larvae collected primarily on the Caribbean coast of Panama. We sequenced mitochondrial cytochrome c oxidase subunit I ( COI ) for 43 species of adult sea urchins to expand the number and coverage of sequences available in GenBank. Sequences were successfully obtained for COI and 16S ribosomal DNA from 272 larvae and assigned to 17 operational taxonomic units (OTUs): 4 from the Pacific coast of Panama, where larvae were not sampled as intensively, and 13 from the Caribbean coast. Of these 17 OTUs, 13 were identified from comparisons with our adult sequences and belonged to species well documented in these regions. Another larva was identified from comparisons with unpublished sequences in the Barcode of Life Database (BOLD) as belonging to Pseudoboletia, a genus scarcely known in the Caribbean and previously unreported in Panama. Three OTUs remained unidentified. Based on larval morphology, at least two of these OTUs appeared to be spatangoids, which are difficult to collect and whose presence often goes undetected in standard surveys of benthic diversity. Despite its ability to capture unanticipated diversity, larval sampling failed to collect some species that are locally common along the Caribbean coast of Panama, such as Leodia sexiesperforata, Diadema antillarum, and Clypeaster rosaceus .